Supervision Arrangements in Order to Strengthen the Protection of Traditional Cultural Expressions as Intellectual Property - Karuna Dewi, Lily; Gde Rudy, Dewa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 2 (2021)DO - 10.24843/JMHU.2021.v10.i02.p04, 2021)
The government is responsible for protecting, not only traditional cultural expressions as part of biodiversity, but also as the property of local communities. Legal regulations related to the aspect of supervision in the protection of traditional cultural expressions have not been explicitly stated in statutory regulations. Regulating aspects of supervision related to the protection of Traditional Cultural Expressions are very important in order to provide a sense of security and comfort to indigenous peoples as owners of these Traditional Cultural Expressions, and to maintain respect for the communal community. The purpose of this paper is to find a juridical basis regarding the supervision of traditional cultural expressions. The research method in the preparation of this article is the normative legal research method, in which this research examines the laws and regulations that are related to legal problems that occur. The results showed that the aspects of supervision in the laws and regulations relating to the protection of traditional cultural expressions have not been regulated in a substantial and detailed manner and only become part of Article 38 paragraph (2) of the Copyright Law. The existence of an aspect of supervision carried out by related parties is very important as part of Article 38 paragraph (3) of the Copyright Law.